The Efficacy of Pyrotinib as a Third- or Higher-Line Treatment in HER2-Positive Metastatic Breast Cancer Patients Exposed to Lapatinib Compared to Lapatinib-Naive Patients: A Real-World Study - Ouyang, D. J; Chen, Q. T; Anwar, M.; Xie, N.; Ouyang, Q. C.; Fan, P. Z.; Qian, L. Y.; Chen, G. N.; Zhou, E. X.; Guo, L.; Gu, X. W.; Ding, B. N.; et al. (Frontiers in Pharmacology, 2021)
Abstract Background: Pyrotinib is a novel irreversible pan-ErbB receptor tyrosine kinase inhibitor. Evidence of the efficacy of pyrotinib-based treatments for HER2-positive metastatic breast cancer (MBC) in patients exposed to lapatinib is limited. Methods: Ninety-four patients who received pyrotinib as a third- or higher-line treatment for HER2-positive MBC were included in this retrospective study. The primary and secondary endpoints were overall survival (OS) and progression‐free survival (PFS). Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) analysis were implemented to balance important patient characteristics between groups. Results: Thirty (31.9%) patients were pretreated with lapatinib and subsequently received pyrotinib as an anti-HER2 treatment, and 64 (68.1%) patients did not receive this treatment. The OS and PFS indicated a beneficial trend in lapatinib-naïve group compared to lapatinib-treated group in either the original cohort (PFS: 9.02 vs 6.36 months, P = 0.05; OS: 20.73 vs 14.35 months, P = 0.08) or the PSM (PFS: 9.02 vs 6.08 months, P = 0.07; OS: 19.07 vs 18.00 months, P = 0.61)/IPTW (PFS: 9.90 vs 6.17 months, P = 0.05; OS: 19.53 vs 15.10 months, P = 0.08) cohorts. Subgroup analyses demonstrated lapatinib treatment-related differences in PFS in the premenopausal subgroup and the no prior trastuzumab treatment subgroup, but no significant differences were observed in OS. Conclusion: Pyrotinib-based therapy demonstrated promising effects in HER2-positive MBC patients in a real-world study, especially in lapatinib-naïve patients, and also some activity in lapatinib-treated patients.